The GWCT Grey Partridge Recovery Programme: a Species Action Plan in Action - Nicholas J. Aebischer (National Quail Symposium Proceedings, 2017)
In 1994, the UK government launched its Biodiversity Action Plan (BAP). Its list of BAP species included the grey partridge Perdix perdix, whose UK numbers had declined by 91% since 1962. The government set numerical targets in its grey partridge Species Action Plan, then nominated the Game & Wildlife Conservation Trust (GWCT) as lead partner to take the Plan forward. To this end, the GWCT has sought to raise awareness of the issues among the farming and shooting communities with promotional material. It has encouraged land and shoot managers to join its Partridge Count Scheme and established local Partridge Groups as a focus for information dissemination, guiding management with local targets set using landscape characteristics to estimate the potential distribution of grey partridges at the 1-km^2 level. Leading by example, the GWCT has demonstrated on the ground how appropriate management leads to successful grey partridge recovery, and it has initiated research into optimal methods of re-establishing grey partridges in areas of extinction. I consider the current population status of the grey partridge in the UK, review the targets of the Species Action Plan in the light of that status, and discuss the chances of success.
Keywords: action plan; grey partridge; Perdix perdix; population recovery; UK